A Transitivity Analysis of Short Story ‘Reunion’ by John Cheever Using NVivo - Anis Khoirunnisa Syahrussalamah; Sumarsih Sumarsih; Gisna Auliya (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2026)
The purpose of this research is to find the process type found in the short story titled ‘Reunion’ by John Cheever and identifies which process types are dominant in the text. The method used in this research is qualitative descriptive. Data collection involves obtaining the text from the online source, segmenting it into clauses, coding techniques, and analyzing the data. The researcher applied the systemic functional linguistic theory presented by Halliday for transitivity analysis of the text. Clauses from the short story were coded and analyzed using NVivo software to ensure systematic classification. The findings reveal five types of transitivity processes: Material (35 clauses), Verbal (21 clauses), Relational (19 clauses), Mental (18 clauses), and Existential (2 clauses). Therefore, Material process is the dominant used type process in the short story text which means this text contains many actions or physical activities and events carried out by the characters in it. These findings contribute to a deeper understanding of how transitivity patterns construct meaning in literary texts and demonstrate the usefulness of Systemic Functional Linguistics (SFL) for literary discourse analysis.